Blasting in mining new trends : workshop hosted by Fragblast 10 : the 10th International Symposium on Rock Fragmentation by Blasting, New Delhi, India, 24-25 November, 2012 /: new trends : workshop hosted by Fragblast 10 : the 10th International Symposium on Rock Fragmentation by Blasting, New Delhi, India, 24-25 November, 2012. (2013) - Unknown
No abstract available